Combined targeting of TGF-β, EGFR and HER2 suppresses lymphangiogenesis and metastasis in a pancreatic cancer model. Issue 1 (28th August 2016) - Gore, Jesse; Imasuen-Williams, Imade E.; Conteh, Abass M.; Craven, Kelly E.; Cheng, Monica; Korc, Murray
Highlights: PDACs with an angiogenic gene signature are enriched in lymphangiogenic genes. Tumors from the KRC PDAC model harbor LECs and have a lymphangiogenic profile. Pancreatic cancer cells from KRC tumors express and secrete lymphangiogenic factors. Targeting TβRI and EGFR/HER2 pathways together is beneficial in KRC mice. Abstract: Pancreatic ductal adenocarcinomas (PDACs) are aggressive with frequent lymphatic spread. By analysis of data from The Cancer Genome Atlas, we determined that 35% of PDACs have a pro-angiogenic gene signature. We now show that the same PDACs exhibit increased expression of lymphangiogenic genes and lymphatic endothelial cell (LEC) markers, and that LEC abundance in human PDACs correlates with endothelial cell microvessel density. Lymphangiogenic genes and LECs are also elevated in murine PDACs arising in the KRC (mutated Kras; deleted RB) and KIC (mutated Kras; deleted INK4a) genetic models. Moreover, pancreatic cancer cells (PCCs) derived from KRC tumors express and secrete high levels of lymphangiogenic factors, including the EGF receptor ligand, amphiregulin. Importantly, TGF-β1 increases lymphangiogenic genes and amphiregulin expression in KRC PCCs but not in murine PCCs that lack SMAD4, and combinatorial targeting of the TGF-β type I receptor (TβRI) with LY2157299 and EGFR/HER2 with lapatinib suppresses tumor growth and metastasis in a syngeneic orthotopic model, and attenuates tumor lymphangiogenesis and angiogenesis while reducing lymphangiogenic genes and amphiregulin and enhancing apoptosis. Therefore, this combination could be beneficial in PDACs with lymphangiogenic or angiogenic gene signatures.